Effects of active exergames on physical performance in older people: an overview of systematic reviews and meta-analysis - Hernandez-Martinez, Jordan; Ramos-Espinoza, Francisco; Muñoz-Vásquez, Cristopher; Guzman-Muñoz, Eduardo; Herrera-Valenzuela, Tomas; Branco, Braulio Henrique Magnani; Castillo-Cerda, Maria; Valdés-Badilla, Pablo (Frontiers in Public Health, 2024)
This overview assessed the available body of published peer-reviewed systematic reviews and meta-analysis related to the effects of active exergames compared with active/passive control on physical performance outcomes in older people. The methodological quality and certainty of evidence were assessed using PRISMA, AMSTAR 2, and GRADE. The protocol was registered in PROSPERO (code: CRD42023391694). The main outcomes indicate that 4,477 records, five systematic reviews, and ten meta-analysis were included. The AMSTAR-2 reported six meta-analyses with high methodological quality, four moderate quality, two systematic reviews with low quality, and three very-low quality. Meta-analysis was performed on balance using the Berg Balance Scale (BBS) and Timed Up-and-Go (TUG) test, on cardiorespiratory fitness using the 6-minute walk test, on upper and lower limbs muscle strength using the handgrip strength, knee extension, and 30-second chair stand tests. Significant differences in favor of the active exergames groups concerning active/passive groups were reported in BBS (SMD= 0.85; 95% CI= 0.12 to 1.58; I2= 96%; p= 0.02), TUG (SMD= 1.44; 95% CI= 0.71 to 2.16; I2= 97%; p< 0.0001) and 30-second chair stand test (SMD= 0.79; 95% CI= 0.33 to 1.25; I2= 88%; p= 0.0008). However, no significant differences were reported in favor of the active exergames groups in 6-minute walk test (SMD= 0.93; 95% CI= -0.64 to 2.50; I2= 95%; p= 0.24), handgrip strength (SMD= 0.67; 95% CI= -0.04 to 1.38; I2= 84%; p= 0.06) and knee extension (SMD= 0.20; 95% CI= -0.05 to 0.44; I2= 95%; p= 0.12) compared to active/passive control. However, it was impossible to perform a meta-analysis for the variables of walking speed as a fall risk due to the diversity of instruments and the small number of systematic reviews with meta-analysis. In conclusion, interventions utilizing active exergames have shown significant improvements in the static and dynamic balance and lower limb muscle strength of apparently healthy older people, compared to control groups of active/inactive participants, as measured by BBS, TUG, and 30-second chair stand tests. However, no significant differences were found in the 6-minute walk, HGS, and knee extension tests.